Spatial and temporal assessment of marine water quality using statistical approaches - Firdaus Mohamad Hamzah; Mohd Nabil Fikri; Mohd Saifullah Rusiman; Mohd Khairul Amri Kamarudin; Shamsul Rijal Muhammad Sabri (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study was carried out to determine the classes and parameters that influence the water quality in the Straits of Johor using the Marine Water Quality Index (MWQI) method and the multi-variable statistical analysis, namely Principal Component Analysis (PCA). The MWQI method classifies the data sets according to four classes of contaminated, medium, good and very good classes. The data were studied from 2016 to 2017 according to two monsoon seasons - the northeast and southwest monsoons. The results for both seasons were compared to find out the difference. The results of the PCA analysis show the relationships between the parameters studied and determine which parameters are responsible for changing water quality standards. The results of the MWQI method reveals that all stations except WQ14 is in class 3 which is moderated while only WQ14 is in class 4 (contaminated). In terms of monsoon, the results of the analysis at the southwest monsoon station found that 25 out of 35 data were in class 3 while the other 10 were in class 4. In addition, MWQI analysis on the northeast monsoon found that 34 out of 35 data were in class 3 and only one was in class 4. These results show that the water quality in the northeast monsoon is better than in the southwest monsoon. The results from the PCA analysis indicates that fecal coliform, total suspended solids and phosphate influence the water quality at the southwest station while the dissolved oxygen and phosphate parameters influence the water quality at the northeast station due to high positive load values. In conclusion, MWQI was able to determine the class of water whilst PCA allowed the identification of types of parameters that affect the water quality. In conclusion, the two above methods can be used to determine pollution levels in water bodies.